A Comprehensive Review on Distribution, Pharmacological Properties, and Mechanisms of Action of Sesamin. (17th August 2022) - Zhang, Yao; Liu, Fen; Lin, Yan; Li, Linhai; Chen, Mingfeng; Ni, Lin
Abstract : Sesamin is a kind of fat-soluble lignan extracted from sesame seeds or other plants. It has attracted more and more attention because of its extensive pharmacological activities. In this study, we systematically summarized the pharmacological activities of sesamin including antioxidant, anti-inflammatory, anticancer, protection of liver and kidney, prevention of diabetes, hypertension, and atherosclerosis. Studies focus on the abilities of sesamin to attenuate oxidative stress by reducing the levels of ROS and MDA, to inhibit the release of pro-inflammatory cytokines (TNF- α, IL-1 β, IL-6, etc.), and to induce apoptosis and autophagy in cancer cells through a variety of signaling pathways such as NF- κ B, JNK, p38 MAPK, PI3K/AKT, caspase-3, and p53. By inhibiting the production of ROS, sesamin can also enhance the biological activities of NO in blood vessels, improve endothelial dysfunction and hypertension, and change the process of atherosclerotic lesion formation. In line with this, the various pharmacological properties of sesamin have been discussed in this review so that we can have a deeper understanding of the pharmacological activities of sesamin and clear the future development direction of sesamin.